(untitled) (Research, Society and Development, 2022)
This article deals with the way in which pesticides are used and how the packaging is discarded, approaching the theme through scientific bases. The use of these inputs in Brazil has been considered a terrifying subject, due to the high concentration of these products in food, consumed by the population and at the same time released into the environment, causing soil, groundwater and river pollution and disregarding the legislation. environmental. What makes this issue even more worrying is the fact that the disposal of packaging in many cases is not being carried out properly, becoming a problem for both health and the environment. In this way, it was necessary to understand the correct disposal of packaging and pesticide residues in Brazil, emphasizing the reverse logistics process promoting the collection, recycling, treatment and/or final disposal of residues, explaining the regulations that governs the use of pesticides in the country, in addition to addressing the risks and damage to public health and the environment. The present work aimed to analyze the appropriate methods of handling pesticide packaging and how the country has been using these inputs, in order to warn about the harm to the environment and health, where we had to demonstrate the increase in the use of pesticides. pesticide in the country in recent decades, the proper way of disposing of packaging from pesticides, emphasizing the main laws that govern the commercialization, inspection and control sectors of agricultural pesticides, the classification of pesticides, in addition to the main damages to human health and the environment. environment. Therefore, it was found that the commercialization system of these chemical products is still in theory a problem for the country’s inspection sector, pesticides that are banned worldwide are still marketed by the black market and used in crops, causing serious damage to people who are exposed to the product of the ecosystem over the years. Therefore, it was necessary to understand and understand the laws and decrees that govern the use of these pesticides and recommendations on the reverse logistics system, which is nothing more than the return of packaging of toxic products to duly legalized companies for proper storage of that material.